The knowledge of pregnant women about polymerase chain reaction HIV testing of infants in the Molemole Municipality of the Capricorn District, Limpopo Province - Ramoraswi, Sophy Ramadimetja (University of Limpopo (Turfloop Campus), 2013)
All pregnant women who seek antenatal health care at the public clinics are offered HIV counselling and testing. Those who agree to test and who test positive, often fail to bring their infants for polymerase chain reaction (PCR) HIV testing after delivery, despite the fact that they have been advised to do so during delivery. There are very few studies which have assessed the women’s knowledge with regard to the PCR HIV testing of infants. In this study; a qualitative, exploratory, and descriptive methodology was applied to explore and describe the knowledge of pregnant women with regard to PCR HIV testing of infants in the Molemole Municipality of the Limpopo Province, Capricorn District. Purposive sampling was used and semi-structured interviews were conducted until saturation of data was reached. Qualitative data analysis design of Marshall and Rossman was used. The study indicated that the participants had knowledge with regard to the PCR HIV testing of infants. The nurse and lay counsellors knew about the different modes of prevention of mother-to-child transmission (PMTCT) and they used every contact opportunity with pregnant women to share its benefits. Mother to mother support groups for HIV positive pregnant and lactating women should be established for continuous support and counselling with the purpose of achieving an HIV-free generation.
Thesis (M.Cur.) --University of Limpopo, 2013
Keywords: Antenatal health care; HIV counselling and testing; 362.19; HIV-positive children; Polymerace chain reaction -- Diagnostic use